Proceedings of the 21st International Conference on Intelligent User Interfaces 2016
DOI: 10.1145/2856767.2856771
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Privacy Concerns on Privacy Recommenders

Abstract: Location-sharing services such as Facebook and Foursquare/Swarm have become increasingly popular, due to the ease at which users can share their locations, and participate in services, games and other applications that leverage these locations. But it is important for people who use these services to configure appropriate location-privacy preferences so that they can control to whom they want to share their location information. Manually configuring these preferences may be burdensome and confusing, and so loc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 26 publications
0
6
0
1
Order By: Relevance
“…More importantly, it does not need the support of a central server. In our previous user study [42], we have found significant privacy concerns from users about providing their data to a central server and such concerns have negative effects on users' perceived recommendation quality, satisfaction, and acceptance of recommendations. Decentralisation enables us to remove the source of such concerns.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…More importantly, it does not need the support of a central server. In our previous user study [42], we have found significant privacy concerns from users about providing their data to a central server and such concerns have negative effects on users' perceived recommendation quality, satisfaction, and acceptance of recommendations. Decentralisation enables us to remove the source of such concerns.…”
Section: Discussionmentioning
confidence: 98%
“…To alleviate the negative effects of people's privacy concerns about providing their data to a centralised recommender [42], in contrast to the existing works, we investigate the feasibility of deploying a location-privacy recommender in a decentralised fashion. In addition, compared with other proposed decentralised recommender systems [13,24,33], we demonstrate the vulnerability of decentralised recommender to sampling attacks, as explained in the next subsection, and propose a reputation scheme that mitigates the effectiveness of such attacks.…”
Section: Location-privacy Recommendersmentioning
confidence: 99%
See 1 more Smart Citation
“…This has gone beyond the findings of prior research. For example, Zhao et al's study has revealed that users' subjective factor about perceived quality of system acts as a mediator between users' concern and acceptance of the system [88], but it was not illustrated what factors are included in the quality of the system. The mediators identified in our study combine the aspects of both users and e-learning systems, reflecting both system-specific features (i.e., confirmed fit, utilization) and user-specific experience (i.e., learning experience, reading experience).…”
Section: Mediatorsmentioning
confidence: 99%
“…Privacy intermediaries and recommendation-based systems for consent have been explored in [1,12,81] including for collecting consent decisions under a single interface [41,49], simplifying privacy policies [7] or automating decision making [4,41]. From our review, we identified four main categories of approach: First, community or crowd-based systems are either community-based projects such asTerms of Service; Didn't Read (ToS;DR) [63] or privacy intermediaries that use crowd-sourcing approaches to support users to make data permission decisions [42,45].…”
Section: Consent Trust and Intermediariesmentioning
confidence: 99%